2022
DOI: 10.1002/bse.2974
|View full text |Cite
|
Sign up to set email alerts
|

Climate change commitment, credit risk and the country's environmental performance: Empirical evidence from a sample of international banks

Abstract: This paper analyses whether banks with a greater commitment to climate change issues, proxied by the climate change score from the Carbon Disclosure Project (CDP), experience an impact on their credit risk and whether this relationship is moderated by the environmental performance of the country where the bank is located. For these purposes, a panel data analysis is carried out on a large sample of international listed banks over the period 2011–2019. Our findings suggest that the commitment to climate issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 100 publications
4
13
0
Order By: Relevance
“…In addition, the result also shows that the education of the farmers increases the probability of full loan repayment, suggesting that education is an important variable in loan repayment during a pandemic. This result is expected and supported in the literature (Birindelli et al ., 2022). This is because most information concerning loan processes given to farmers during the pandemic requires a literate audience that is conversant with online information because of fear of contracting the disease in the banks (Pan et al ., 2021).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the result also shows that the education of the farmers increases the probability of full loan repayment, suggesting that education is an important variable in loan repayment during a pandemic. This result is expected and supported in the literature (Birindelli et al ., 2022). This is because most information concerning loan processes given to farmers during the pandemic requires a literate audience that is conversant with online information because of fear of contracting the disease in the banks (Pan et al ., 2021).…”
Section: Resultssupporting
confidence: 92%
“…From this theory, banks must undertake rigorous assessments and reviews of all loan applications and even detect the ones that other financial institutions have rejected (Udom and Onyekachi, 2018). In addition, studies have shown that loan repayment performance is influenced by banks, borrowers' characteristics and macroeconomic variables (Birindelli et al ., 2022). Based on this theoretical framework, the study used an analytical model in which the lending performance of formal financial institutions is a function of bank and customers' characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Both banks recorded relatively better business results than their competitors in 2020. This conclusion is in line with the results achieved by (Birindelli et al 2022). At the same time, they are global banks owned by strategic investors, from France and the Netherlands, leading global initiatives to reduce CO 2 emissions.…”
Section: Discussionsupporting
confidence: 88%
“…Both banks recorded relatively better business results than their competitors in 2020. This conclusion is in line with the results achieved by (Birindelli et al 2022). At the same time, they are global banks owned by strategic investors, from France and the When analysing the dendrograms with regard to the differences between the individual nodes, four main clusters can be identified, in which clusters III (banks C_7, C_11 and C_12) and IV (banks C_5 and C_10) are identical for both methods.…”
Section: Discussionsupporting
confidence: 87%
“…The issue of climate risk has received increasing attention from scholars in recent years, and many studies have begun to analyze the relationship between climate risk and the financial system, including the credit supply (Clarvis et al, 2014; Oguntuase, 2020 ; Da Mata & Resende, 2020 ; Christophers et al, 2020 ; Nwani & Omoke, 2020 ; Birindelli et al, 2022 ), the governance of fund markets (Bowman & Minas, 2019 ; Cui & Huang, 2018 ; Lu et al, 2022 ), the insurance institutions’ responsibility (Surminski et al, 2016 ) and so on. Campiglio et al ( 2018 ) recognize that climate risks cause losses to the balance sheets of financial market players, leading to the repricing of carbon-intensive assets and threatening the stability of financial markets.…”
Section: Introductionmentioning
confidence: 99%